2021
DOI: 10.22159/ijap.2021v13i1.40054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Solubility and Dissolution Rate of Acetylsalicylic Acid via Co-Crystallization Technique: A Novel Asa-Valine Cocrystal

Abstract: Objective: This study aims to synthesize acetylsalicylic acid (ASA) cocrystals using valine as a coformer via a co-crystallization technique to increase the solubility and dissolution rate of ASA. Methods: The ASA-valine cocrystal (1:1 molar ratio) was prepared using the solvent evaporation technique with ethanol: water (50:50). The cocrystal was characterized using Fourier transform infrared spectroscopy (FT-IR), Differential scanning calorimetry (DSC), Powder X-ray diffraction (PXRD), Scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…From the literature it can be concluded that rough particles produce less stable emulsion droplets compared to smooth spherical particles due to reduced contact between particle and interface, resulting in lower adsorption energy of the rough particles [29]. Therefore, spherical nanoparticles contribute to better formulation stability by reducing antiparticle friction due to the smooth surface [30].…”
Section: Discussionmentioning
confidence: 99%
“…From the literature it can be concluded that rough particles produce less stable emulsion droplets compared to smooth spherical particles due to reduced contact between particle and interface, resulting in lower adsorption energy of the rough particles [29]. Therefore, spherical nanoparticles contribute to better formulation stability by reducing antiparticle friction due to the smooth surface [30].…”
Section: Discussionmentioning
confidence: 99%
“…One of which is acetosal (acetylsalicylic acid) or often known as aspirin (Kuntari, Aprianto, Noor, & Baruji, 2017). Acetosal is a drug in the Biopharmaceutical Classification System (BCS) class II group (low solubility, high permeability) (Shanthala et al, 2021). Low solubility affects absorption because it causes a decreased dissolution rate (Noval & Rosyifa, 2021).…”
Section: Introductionmentioning
confidence: 99%